OPTIMALISASI PENDIDIKAN AKHLAK PADA ANAK USIA SEKOLAH DASAR - Hairul Huda (Universitas Muhammadiyah Jember, 2018)
Children are usually considered to maintain good behavior if they act in accordance with religious values (e.g., performing five prayers daily, fasting during the entire month of Ramadhan, being respectful and obedient to their parents, etc.). With respect to the latter (i.e., moral education), it is generally associated with tarbiyah since both aim to develop children’s noble character and proper behavior. There are, however, different ways as to how a certain group of community attempt to develop such character and behavior among children. People living in Bagon Kedung Sumur, for instance, have long carried out moral education for their younger generation by developing and reinforcing behaviors that appear to conform their religious beliefs (e.g., nurturing noble dispositions, requiring five prayers and other religious practices as well as sharpening children’s intellectual and social quotient). The goal of these efforts are to enable children to develop behavior that conforms with the community’s religious beliefs and set of values, all of which are deemed critical as a basis for children to act properly and acceptably within their community. Keyword : optimization, moral education, primary school age children